1979
DOI: 10.1007/bf00450223
|View full text |Cite
|
Sign up to set email alerts
|

Fresh immature articular cartilage allografts

Abstract: The integration of immature cartilage allografts to knee joints of both normal rabbits and those submitted to arthritis through papain was studied for a period of up to 9 months. Two types of grafts were compared: chondral--constituted only by cartilage, and osteochondral--cartilage plus a thin layer of subchondral bone. The integration of the grafts was analyzed through inspection of the articular surface and histologic sections. The viability of the grafts was checked through the incorporation of 35SO4 on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…coordination there was a single of chondrocyte and in some part cluster of cells was observed in group I animals (mals group I (control) was quite less than which was observed in grafted groups. There was a single row of chondrocytes and in some part cluster of cells was observed in group I animals [7] Fibrocartilage of cartilage defected area with increasing full thickness of cartilage have been reported in horses [8][9][10] . There was a similar report [7] at knee joint of rabbit.There was complete and uniform hyaline cartilage in group II animals which was indicative for foetal skull bone reparative cartilagenous cells to remodel itself into hyaline cartilage with active matrix layer [11,12] Klilson [13] reported that following increase in This study indicated that there was full thickness cartilage like tissues which was originated from foetal skull bone having mesenchymal tissues which further modify itself into cartilage in suitable environment.…”
Section: Discussionmentioning
confidence: 99%
“…coordination there was a single of chondrocyte and in some part cluster of cells was observed in group I animals (mals group I (control) was quite less than which was observed in grafted groups. There was a single row of chondrocytes and in some part cluster of cells was observed in group I animals [7] Fibrocartilage of cartilage defected area with increasing full thickness of cartilage have been reported in horses [8][9][10] . There was a similar report [7] at knee joint of rabbit.There was complete and uniform hyaline cartilage in group II animals which was indicative for foetal skull bone reparative cartilagenous cells to remodel itself into hyaline cartilage with active matrix layer [11,12] Klilson [13] reported that following increase in This study indicated that there was full thickness cartilage like tissues which was originated from foetal skull bone having mesenchymal tissues which further modify itself into cartilage in suitable environment.…”
Section: Discussionmentioning
confidence: 99%